The Effect of Vertical Mergers and Acquisitions (M&A) on the Value of Global Energy Sector Companies - Rusyda, Rania; Prijadi, Ruslan (Syntax Literate, 2025)
This study aims to analyze the impact of vertical mergers and acquisitions (M&A) on firm value in the global energy sector, distinguishing vertical integration into upstream, downstream, and other categories. The background of this research is that, in the energy sector, most companies tend to acquire target firms operating in the same sector. This study adopts a quantitative approach by collecting data from Refinitiv and S&P Capital. The data consists of energy companies engaged in M&A activities during the 2014-2018 period and evaluates their impact on firm value over five years following the transactions. A total of 443 deals were analyzed using the Difference-in-Differences (DID) method. The results indicate that upstream and other vertical integrations have a significant positive impact on firm value, while downstream vertical integration shows a significant negative impact on firm value.